2021
DOI: 10.2147/jmdh.s270394
|View full text |Cite
|
Sign up to set email alerts
|

Degrees of Multidisciplinarity Underpinning Care Planning for Patients with Cancer in Weekly Multidisciplinary Team Meetings: Conversation Analysis

Abstract: Purpose Despite an increase in research on multidisciplinary team (MDT) meetings, the implementation of MDT-driven decision-making, ie, its fidelity, remains unstudied. We report fidelity using an observational protocol measuring degree to which MDTs in their weekly meetings in the UK adhere to 1) the stages of group decision-making as per the ‘Orientation-Discussion-Decision-Implementation’ framework, and 2) cancer guidelines on the composition and characteristics of their weekly meetings produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…The reasons for growing workload are numerous, including increased cancer incidence, cancer survival, comorbidities, population size, and longevity [11,[25][26][27][28][29]. In addition, perhaps due to the success of the MDT model, many straightforward or non-cancerous cases are put through the MDT meeting [30]. It appears that healthcare professionals appreciate the benefits of the MDT and feel confident in the safety net it provides for a range of cases, although there are growing concerns that clinicians now fear making clinical decisions without the approval of the MDT [31].…”
Section: Challenges To Mdt Meeting Effectivenessmentioning
confidence: 99%
“…The reasons for growing workload are numerous, including increased cancer incidence, cancer survival, comorbidities, population size, and longevity [11,[25][26][27][28][29]. In addition, perhaps due to the success of the MDT model, many straightforward or non-cancerous cases are put through the MDT meeting [30]. It appears that healthcare professionals appreciate the benefits of the MDT and feel confident in the safety net it provides for a range of cases, although there are growing concerns that clinicians now fear making clinical decisions without the approval of the MDT [31].…”
Section: Challenges To Mdt Meeting Effectivenessmentioning
confidence: 99%
“…Study results from literature demonstrate that this phase is sometimes omitted, such that in these cases the common basis for the decision is not established. 23 In the majority of cases in the present study, information was reported in a neutral manner, whereas other reports included comments or assessments. While Hamilton et al 28 observed that treatment options were expressed in a non-neutral manner to patients and that the framing effect thus influenced decisions, the study noted that healthcare providers frequently also use such a non-neutral form of presentation when reporting to other healthcare providers.…”
Section: Discussionmentioning
confidence: 82%
“… 22 In another study, also using conversation analysis, 4% of case discussions in MTBs in breast cancer care directly started with the discussion, and in MTBs in gynecological cancer care, in 4% of case discussions the decision was not articulated. 23 …”
Section: Introductionmentioning
confidence: 99%
“…In terms of the MDM decision‐making processes, patient‐centred care was included as a criterion in the guideline by Taylor et al, 13 whilst the guideline by Ottevanger et al 10 had an additional focus on the documentation of decisions made at MDMs. The importance of these guidelines was emphasised by an observational study by Soukup et al noting that more than half the case reviews take place between only two or three disciplines in the meetings 15 …”
Section: Resultsmentioning
confidence: 99%
“…The importance of these guidelines was emphasised by an observational study by Soukup et al noting that more than half the case reviews take place between only two or three disciplines in the meetings. 15 One study explored the role of streamlining patient discussions as opposed to discussing every patient. 16 The authors defined streamlining discussion as enabling the prioritisation of more complex cases during MDMs over straightforward cases, which can be discussed briefly, or excluded from MDMs altogether.…”
Section: The Optimal Structure Of Mdmsmentioning
confidence: 99%